Priority setting towards achieving under-five mortality target in Africa in context of sustainable development goals: an ordinary least squares (OLS) analysis - Michael Acheampong; Chukwudi Ejiofor; Abraham Salinas-Miranda; Bryana Wall; Qiuyan Yu (BMC, 2019)
Abstract Background Africa reduced its under-5 mortality rate (U5MR) by more than 50% during the MDGs era. However, it still has by far the highest average U5MR in the world - 81 deaths compared to a global average of 43 deaths per 1000 births, with eight of the ten countries in the world with the highest child mortality rates. The primary objective of our study was to examine the socioeconomic, healthcare, and environmental determinants that most account for U5MR disparities between African countries. Methods We used a series of ordinary least squares (OLS) regression models to assess the effects of 14 distinct socioeconomic, environmental and healthcare variables that account for the high U5MR differentials that persist between African countries. We conducted our analysis on 43 countries for which data were available. Using a dummy variable, we also emphasized factors that may be accounting for the disparity between the eight worst-performing countries and the remainder of the continent. Results Among all the determinants analyzed in our study, the results reveal that the factors that most account for the inequities observed are, in order, expenditure on healthcare (p < 0.01), total fertility rate (p < 0.01), income per capita (p < 0.05), and access to clean water (p < 0.1). Conclusions Our results show that the gap between the best and worst performing countries in Africa can be significantly narrowed if government and donor interventions will target downstream factors such as improving education for mothers and sensitising them about birth control since fertility rate differences play a critical role. Improving accessibility to clean water sources to reduce outbreaks of diarrhea diseases is also observed as a critical factor.